One- or two-step? New insights into two-step hypothesis and rainbow-like theory for pitch class–color synesthesia - Cao, Ang; Ueda, Kazuhiro (Frontiers in Psychology, 2025)
IntroductionThis study investigates the mechanisms underlying pitch class–color synesthesia, a cognitive trait in which musical pitches evoke color perceptions. Synesthesia in music particularly involves the association of pitch classes (e.g., do, re, and mi) with specific colors. A previous study introduced the two-step hypothesis, which suggests that pitch class identification precedes color association, and proposed a rainbow-like theory based on color gradients selected by synesthetes. The primary objective is to retest these theories to evaluate their generalizability in explaining pitch class–color synesthesia.MethodsWe employed a dual-task paradigm to assess the robustness of the two-step hypothesis and conducted qualitative interviews to explore the nature of synesthetic experiences.ResultsThe results indicated that the two-step hypothesis may not be always applicable, because it effectively accounts for only a subset of synesthetes. The presence of one-step synesthetes, who experience direct pitch-to-color associations without intermediate steps, implied a more varied synesthetic mechanism. Moreover, rainbow-like theory predominantly characterized two-step synesthetes, while one-step synesthetes exhibited distinct color perceptions. Furthermore, we found that the differentiation between two- and one-step synesthesia may be associated with the methods through which participants develop synesthetic associations.DiscussionThe findings highlighted the diversity of synesthetic experiences in pitch class-color synesthesia, which challenges the generalizability of the current theories and poses the need for a further nuanced understanding of this phenomenon.